2001
DOI: 10.1254/jjp.87.151
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Inflammatory Cell Infiltration Inhibitor IS-741 on Colitis Induced by Dextran Sulfate Sodium in the Rat

Abstract: ABSTRACT-We examined the therapeutic effects of the inflammatory cell infiltration inhibitor IS-741 (N-(2-((ethylsulfonyl)amino)-5-(trifluoromethyl)-3-pyridinyl)-cyclohexanecarboxamide monosodium salt monohydrate) on a rat colitis model. As a result of its effects on leukocyte infiltration, IS-741 inhibits cell adhesion, alleviates symptoms and signs of pancreatitis and multiple organ failure and demonstrates a lifesaving effect in a model of severe acute pancreatitis. A rat model was prepared by inducing coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…In the experimental rat model for colitis, pathological changes such as inflammatory cell infiltration, edema, hemorrhage and metaplasia were observed in the muscularis mucosae of the large intestine (Yotsuya et al, 2001). As a new therapeutic target for inflammatory bowel diseases such as diarrhea, constipation, irritable bowel syndrome and Crohn's disease (Kirsner, 2000;Van Montfrans et al, 2002;Lembo and Camilleri, 2003;Mertz, 2003), much attention should be attracted to the motor regulation of the intestinal muscularis mucosae.…”
Section: Discussionmentioning
confidence: 99%
“…In the experimental rat model for colitis, pathological changes such as inflammatory cell infiltration, edema, hemorrhage and metaplasia were observed in the muscularis mucosae of the large intestine (Yotsuya et al, 2001). As a new therapeutic target for inflammatory bowel diseases such as diarrhea, constipation, irritable bowel syndrome and Crohn's disease (Kirsner, 2000;Van Montfrans et al, 2002;Lembo and Camilleri, 2003;Mertz, 2003), much attention should be attracted to the motor regulation of the intestinal muscularis mucosae.…”
Section: Discussionmentioning
confidence: 99%
“…29 Yamauchi et al 20 reported that IS-741 inhibited the leukocyte adherence to pancreatic collecting venules, accompanied by a reduction in Mac-1 expression on circulating neutrophils in acute necrotizing pancreatitis animals. Yotsuya et al 30 suggested that IS-741 inhibited the cluster formation of LFA-1 with activation of LFA-1. In previous studies, IS-741 has been proven to have therapeutic effects in some animal models of acute pancreatitis, 20,22 ileitis, 23 and colitis, 19,24 and it is supposed that the mechanism by which IS-741 prevents the development of inflammation might be due to its inhibitory effects on the adhesion of neutrophils to endothelial cells and subsequent neutrophil infiltration into the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yotsuya et al 19 reported that the administration of IS-741 (1, 10, or 100mg/kg) led to the attenuation of dextran sodium sulfate (DSS)-induced colitis, which is useful for the evaluation of therapeutic effects against ulcerative colitis. They showed that IS-741 decreased the area of erosion in the large intestine and decreased the thickening of the large intestinal wall, as well as attenuating anemia, due to its inhibitory effects on the inflammatory cell infiltration into the intestinal wall.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] However, there are only few reports about the efficacy of leukocyte-endothelial interaction inhibitors against intestinal inflammation. 19 In the present study, we investigated the effects of oral IS-741 on rat experimental ileitis. A trinitrobenzene sulfonic acid (TNBS) colitis model was reported by Morris et al, 20 and it has been used as a Crohn's disease colitis model.…”
mentioning
confidence: 99%